2016
DOI: 10.1097/fch.0000000000000085
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of Internal Migration and Substance Use Among an Indigenous Community in Southern Mexico

Abstract: The primary aim of this study was to explore the association between internal migration experience within Mexico and lifetime substance use among a sample of 442 indigenous persons from Yucatan, Mexico. Adjusting for potential confounding, correlates of lifetime substance use were assessed among participants with and without internal migration experience. Internal migration to a tourist destination was independently associated with higher odds (Adjusted Odds Ratio (AOR): 2.1; 95% Confidence Interval (CI): 1.3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…For instance, studies investigating insurance status and stigma by race/ethnicity have found negative, positive, and null associations with substance abuse treatment utilization (Chartier et al, 2016; Schmidt et al, 2006; Schmidt & Weisner, 2005; Smith et al, 2010; Weisner & Matzger, 2002). Further, a broader literature including health services research (e.g., studies of primary care and mental health services) and qualitative and regional studies among Latinos suggest that other factors (e.g., culture, migration experiences) may strongly influence their help-seeking behaviors (Alegría et al, 2006; Alvarez et al, 2007; Amaro et al, 1999; Berk & Schur, 2001; Delgado, 2002; Hacker et al, 2011; Mendoza, 2009; Pagano, 2014; Pagano et al, 2016; Pinedo et al, 2016). However, it remains to be determined how these factors relate to specialty substance abuse treatment and if they differ by race/ethnicity.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, studies investigating insurance status and stigma by race/ethnicity have found negative, positive, and null associations with substance abuse treatment utilization (Chartier et al, 2016; Schmidt et al, 2006; Schmidt & Weisner, 2005; Smith et al, 2010; Weisner & Matzger, 2002). Further, a broader literature including health services research (e.g., studies of primary care and mental health services) and qualitative and regional studies among Latinos suggest that other factors (e.g., culture, migration experiences) may strongly influence their help-seeking behaviors (Alegría et al, 2006; Alvarez et al, 2007; Amaro et al, 1999; Berk & Schur, 2001; Delgado, 2002; Hacker et al, 2011; Mendoza, 2009; Pagano, 2014; Pagano et al, 2016; Pinedo et al, 2016). However, it remains to be determined how these factors relate to specialty substance abuse treatment and if they differ by race/ethnicity.…”
Section: Introductionmentioning
confidence: 99%
“…The environmental availability of alcohol in small towns such as Tunkás is important to note. Our prior work with the Tunkás community indicates a ubiquitous availability of liquor in Tunkás and communities where members migrate, which influences consumption patterns among migrants ( 28 , 29 ). Furthermore, an earlier study conducted by a member of our Investigator team (Dr. Pedro Lewin) indicated that the female head of household whose partner had migrated to the U.S. or elsewhere in Mexico expressed facing stressors such as weakening of their marital relationship, marital difficulties and emotional instability among younger children after their spouses migrated, further indicating the potential negative health impact on the family ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prior research sheds light on why indigenous health might worsen after migration. Some potential explanations include the physical demands of their occupations and poor working conditions (Gamlin & Hawkes, 2015; Juárez-Sánchez, 2015; Melesio Nolasco, 2006), poverty and marginalization (Holmes, 2006; Pérez Ruiz, 2007), changing diets and food insecurity (Maxwell et al, 2015), increased substance use (Pinedo et al, 2014, 2016), and discrimination (Pérez Ruiz, 2007; Salgado et al, 2014). Health deterioration could also be related to the characteristics of the destination community, such as the levels of urbanization and deprivation (Darlington-Pollock et al, 2016, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This research provides insights into the relationship between migration and indigenous health. For instance, indigenous migration to the US is associated with a higher risk for sexually transmitted illnesses (Espinoza et al, 2014; Maier, 2007), increased alcohol and drug use (Pinedo et al, 2014, 2016), poor self-rated health (Holmes, 2006), and higher depressive symptoms (Salgado et al, 2014). These findings are based on cross-sectional research and, thus, it is not possible to establish if their health was directly and negatively impacted by migration or if they experienced poor health before migrating.…”
Section: Introductionmentioning
confidence: 99%